Managing pseudophakic bullous keratopathy with a topical rho kinase inhibitor: a case series - Nir Erdinest; Nadav Shemesh; Yishay Weill; Shani Morad; Itay Nitzan; David Smadja; David Landau; Itay Lavy (Journal of Medical Case Reports)
Abstract Background Cataract surgery is common procedure globally. Among its adverse effects is pseudophakic bullous keratopathy (PBK), a corneal disorder characterized by stromal edema and the formation of epithelial and subepithelial bullae due to endothelial cell loss and decompensation. This case series examines the outcomes of using the topical Rho kinase inhibitor Ripasudil for managing pseudophakic bullous keratopathy (PBK) in three patients treated at Hadassah Medical Center. Clinical data, including visual acuity, intraocular pressure, central corneal thickness (CCT), and endothelial cell count, were extracted from electronic medical records before and after treatment. Patients were treated with topical Ripasudil for periods ranging from three to eleven months, three times daily, with adjustments based on disease severity. Case presentation The first case involved a 66-year-old Jewish female, who presented with persistent corneal edema in the left eye. Following three months of Ripasudil therapy, the patient exhibited notable improvement in best-corrected visual acuity (BCVA), a reduction in central corneal thickness (CCT), and decreased central stromal edema. Similarly, the second case featured a 58-year-old Jewish male with a history of cataract surgery in the right eye performed 3 years prior at an external institution. After 3 months of Ripasudil treatment, the patient demonstrated measurable improvements in both BCVA and CCT, mirroring the therapeutic trend observed in the first case. In parallel, the third case described a 69-year-old Jewish male who presented with a 6-month history of blurred vision. In total, 11 months of Ripasudil administration led to resolution of stromal haze and corneal edema, along with a significant reduction in CCT and an enhancement in BCVA. Conclusion These findings suggest that Ripasudil has potential as an effective treatment option for PBK, possibly delaying or avoiding the need for corneal transplantation. Further studies are required to confirm the long-term efficacy and safety of Ripasudil for PBK.